Analysis and Utilization of the Base64 Algorithm for Image Encryption and Decryption Security in Web-Based Images - Baso, Fadhlirrahman (PT. Lontara Digitech Indonesia, 2023)
Data is often the target of irresponsible people for misuse. The theft is done is to benefit from the person who has the data. In addition to theft of work files, theft is also carried out on image files. The purpose of this file theft is to find out what the image contains. Someone has a private image that cannot be known by others. Misuse of image files will be fatal for the owner of the image. Cryptographic techniques are needed in securing images and one of the methods used to secure these images is using the base64 algorithm. The Caesar Cipher algorithm can help users secure the image file. The Base64 algorithm can be used to change the ASCII 256 format to Base64 so that it is easy to send or store on a storage medium. By applying the Base64 algorithm to image files, the security and confidentiality of these files will protect data from irresponsible people.